Correlates of dietary diversity among children aged 6–23 months of head porters in Ghana - Amoah, Adwoa Nyantakyiwaa; Danquah, Angelina Opoku; Stanislav, Traore Seydou; Drokow, Emmanuel Kwateng; Yacong, Bo; Wang, Ling; Lyu, Quanjun (Frontiers in Public Health, 2022)
Objective In many developing countries, most children cannot meet minimum dietary diversity (MDD), defined as the consumption of four or more of the seven food groups. In Ghana, only 35% of children met MDD nationwide in 2017, but rates are worse among the rural poor and resource-constrained individuals like Head Porters (HPs). The current study investigated the correlates of MDD in children of HPs aged 6–23 months old in Ghana. Methods and materials A cross-sectional survey was carried out in 2021 among 423 HPs selected purposively from eight market centers in two commercial cities. A multi-stage sampling method was used in obtaining the sample, while a structured interview guide was used to collect data from the caregivers. Stata version 15.1 and descriptive and inferential statistics like frequency, percentage, chi-square and logistic regression were used to analyze the data. All results were deemed significant if the p-value was < 0.05 and the odds ratios with a 95% confidence interval. Results The children had a mean age of 14.3 (±4.9) months, while half of the caregivers (48.2%) were between 15 and 25 years. Approximately 59% (251) had good knowledge of infant and young child feeding practices (IYCF). About 45% of the children consumed a diversified diet. The number of postnatal care (PNC) visits, delivery in a health facility, meeting minimum meal frequency (MMF), and the child's age was independently associated with MDD at the multivariate level. Conclusion Over a third of the caregivers had poor knowledge of IYCF practices. Furthermore, less than half of the children achieved MDD reflecting the need for more education by the stakeholders. Regular PNC visits and delivery in health facilities were independently associated with MDD; therefore, interventions to combat low MDD should prioritize the relevance of these predictors.